Assessing home-based rehabilitation within the development of an integrated model of care for people living with HIV in a resource-poor community - Saul Cobbing; Jill Hanass-Hancock; Hellen Myezwa (AOSIS, 2017)
Background: People living with HIV (PLHIV) are living longer lives but are at a greater risk of developing disability. South Africa has the largest antiretroviral therapy (ART) programme in the world, shifting HIV from a deadly to a chronic disease. The integration of rehabilitation into chronic care is therefore now crucial to ensure the highest quality of life of PLHIV. Aim: To describe how a home-based rehabilitation (HBR) programme adhered to the fundamental principles of a theoretical model of integrated care developed for the study setting in KwaZulu-Natal, South Africa. Method: The process and results from the HBR programme were assessed in relation to the model of care to ascertain which principles of the model were addressed with the HBR programme and which elements require further investigation. Results: The HBR programme was able to apply a number of principles such as evidence-based practice, task shifting to lay personnel, enabling patient-centred care and maximising function and independence of PLHIV. Other elements such as the adoption of a multidisciplinary approach, training on the use of disability screening tools and the use of evidence to influence policy development were more difficult to implement. Conclusion: It is possible to implement elements of the integrated model of care. Further research is needed to understand how principles that require further training and collaboration with other stakeholders can be implemented. The results of this study provide additional evidence towards understanding the feasibility of the theoretical model and what is required to adjust and test the full model.